2021
DOI: 10.1177/0972558x211001156
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices About Sexual Health and Its Socioeconomic Correlates Among Adolescent Girls in Sikkim, India

Abstract: Adolescents constitute a quarter of total Indian population. Many of them become sexually active despite being informed of the risks which they may encounter. The present study aims to address knowledge and perception on HIV/AIDS, STIs, and safe sex among adolescent girls (15 to 19years) in Sikkim, India. The study also evaluates their attitudes, and practices of sexual activities among their peer groups. The study is based on randomly selected 1031 unmarried adolescent girls residing in Gangtok, the capital t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The awareness of contraception among teenage girls was discussed in four papers [ 43 , 44 , 62 , 65 ]. Five articles explained the understanding of the use of contraception to prevent unwanted pregnancy [ 14 , 41 , 43 45 ]. Lack of awareness about contraceptive methods and reproductive health was discussed in eight articles [ 44 , 49 , 55 , 56 , 58 , 61 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The awareness of contraception among teenage girls was discussed in four papers [ 43 , 44 , 62 , 65 ]. Five articles explained the understanding of the use of contraception to prevent unwanted pregnancy [ 14 , 41 , 43 45 ]. Lack of awareness about contraceptive methods and reproductive health was discussed in eight articles [ 44 , 49 , 55 , 56 , 58 , 61 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one article reported awareness of the advantage of family planning among adolescent girls [ 60 ]. The sources by which teenagers gained knowledge about safe sex were described in three papers [ 14 , 33 , 41 ]. Gupta et al discussed that the internet and partner were the major sources of information about any sexual activity for adolescent girls [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study ndings were similar to a study carried out in Sikkim, India indicated that adolescent girls' knowledge about STDs other than HIV, safe sex, and condom used remained at low level. The same study revealed that older adolescents knew more about SRH matters compared to young (9).…”
Section: Discussionmentioning
confidence: 80%
“…As estimated by various scholars [ 7 ], one of the main factors influencing people's ability to lead healthy lives is safe sexual behaviours. However, teens (10 to 19 years) are the most susceptible to the negative effects of unprotected sex because, according to UNICEF, these behaviours are linked to two-thirds of adult premature deaths and one-third of the entire burden of diseases [ 8 ]. Drug use, poor parenting, peer pressure, sociocultural standards, mass media, and individual sexual attitudes are all occasionally associated with the behaviours [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%